New Strategy Is Needed to Prevent Pneumococcal Meningitis. Issue 4 (April 2020) - Mukerji, Reshmi; Briles, David E
Abstract : Background: Polysaccharide conjugate vaccines (PCVs) target the pneumococcal capsular types that most commonly cause fatal pneumonia and sepsis. Because these types were eliminated by the vaccines, it became apparent that in immunized populations, most invasive pneumococcal diseases, including bacteremia, sepsis and complicated pneumonia, were greatly reduced. However, the protective effects of PCVs against another invasive disease, meningitis, has shown much less or no decrease in disease incidence. Methods: References were identified through searches of PubMed for articles published from January 1930 to the present by use of specific search terms. Relevant articles were also identified through searches in Google and Google Scholar. Relevant references cited in those articles were also reviewed. Results: Even in the presence of the PCVs, meningitis rates in children have been reported globally to be as high as 13 per 100, 000 annually. Widespread use of vaccines resulted in the emergence of a broad diversity of replacement non-PCV type strains. These strains generally failed to cause sepsis, but caused meningitis of comparable severity and levels similar to, or in excess of, prior pneumococcal meningitis rates. This is probably because these non-PCV type strains do not survive well in the blood, therefore possibly entering the brain through nonhematogenous routes. Conclusions: Because virtually all cases of pneumococcal meningitis lead to either permanent neurologic sequelae or death, it would be well worth the effort to develop a new vaccine capable of preventing pneumococcal meningitis regardless of capsular type. Such a vaccine would need to protect against colonization with most, if not all, pneumococci.